2012
DOI: 10.1371/journal.pone.0047267
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Mild to Moderate Chronic Kidney Disease and Coronary Artery Disease Determined with Coronary CT Angiography

Abstract: BackgroundBoth end-stage and milder stages of chronic kidney disease (CKD) are associated with an increased risk of adverse cardiovascular events. Several studies found an association between decreasing renal function and increasing coronary artery calcification, but it remains unclear if this association is independent from traditional cardiovascular risk factors. Therefore, the aim of this study was to investigate whether mild to moderate CKD is independently associated with coronary plaque burden beyond tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…In contrast, according to Joosen et al, mild-moderate CKD was not independently associated with coronary plaque burden after adjusting for traditional cardiovascular risk factors. 21 We noted similar results to the Dallas Heart Study and CRIC: the presence of CAC and its severity were closely related to decreased eGFR. 4, 6 The association between CAC and eGFR remained significant after adjusting for traditional risk factors.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, according to Joosen et al, mild-moderate CKD was not independently associated with coronary plaque burden after adjusting for traditional cardiovascular risk factors. 21 We noted similar results to the Dallas Heart Study and CRIC: the presence of CAC and its severity were closely related to decreased eGFR. 4, 6 The association between CAC and eGFR remained significant after adjusting for traditional risk factors.…”
Section: Discussionsupporting
confidence: 81%
“…The results of previous studies regarding the change in the coronary plaque volume by CKD are inconsistent (14)(15)(16)(17)(18), and the effect of CKD on the development of coronary stenosis has not yet been elucidated. In the present study, the multiple regression analysis using data from both men and women indicated that the association between the eGFR and the log-GS was marginally significant (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Increased vulnerability of coronary plaque by increased lipid deposition and necrosis within the plaque has been suggested by several studies using integrated backscatter intravascular ultrasound (IB-IVUS) imaging and intracoronary angioscopy (9)(10)(11)(12)(13). In contrast, reported results regarding the change in the coronary plaque volume by CKD in earlier studies are inconsistent (14)(15)(16)(17)(18). However, the numbers of patients with severe renal dysfunction were not large, and the overall severity of coronary artery disease has not been determined for the comparison of patients with and without CKD in those studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although it remains unclear whether impaired renal function is associated with coronary calcification independent of traditional cardiovascular risk factors, the development and progression of calcification seem to be linked to disrupted mineral metabolism in end-stage renal disease [18]. Conversely, other studies demonstrate that decreased renal function is not associated with greater plaque volume or growth, and luminal stenosis [19][20][21]. However, most studies included diabetic patients and did not distinguish diabetic from nondiabetic CKD.…”
Section: Discussionmentioning
confidence: 99%